English Studies in India Contemporary and Evolving Paradigms - Mahanta, Banibrata; Sharma, Rajesh Babu (Springer Nature Singapore : Imprint: Springer, 2019)
This volume is a collection of scholarly papers that explore the complex issues concerning English Studies in the present Indian context. The discussions in this volume range from historical perspectives to classroom-specific pedagogies, from sociological and political hierarchies to the dynamics of intellectual development in the English language environment. Interrogating both policy and practice pertaining to English Studies in the context of Indian society, culture, history, literature and governance, the chapters seek to formulate contemporary perspectives to these debates and envision alternative possibilities. Since the introduction of English to India more than 2 centuries ago, the language has transmuted the very fabric of Indian society, culture, history, literature and governance. The idea of India cannot be conceived in its entirety without taking into consideration the epistemological role that English has played in its formation. The present globalized world order has added dimensions to English Studies which are radically different from those of India's colonial and postcolonial past. It is therefore imperative that the multitudinous shades and shadows of the discipline be re-examined with inputs drawn from the present context. This volume is for scholars and researchers of English literature and language studies, linguistics, and culture studies, and others interested in exploring new paradigms of engagement with the disciplinary formulation of English Studies in India.